A chronological framework for the Clyde Foreland Formation, Eastern Canadian Arctic, derived from amino acid racemization and cosmogenic radionuclides - Refsnider,KA; Miller,GH; Fréchette,B; Rood,DH (Quaternary Geochronology, 2013)
The most extensive terrestrial outcrops of glacial and glaciomarine deposits in the Eastern Canadian Arctic are exposed in sea cliffs along the Clyde Foreland and Qivitu Peninsula of Baffin Island. Collectively known as the Clyde Foreland Formation (CFF), these stacked deposits record at least seven glacial advances. Despite having been the focus of numerous investigations spanning nearly 50 years, no numerical chronological framework for the age of the deposits has been established. Previous studies relied on biostratigraphy and amino acid racemization (AAR) geochronology and postulated that the oldest units were Late Pliocene to Mid-Pleistocene in age. In this paper, we use a cosmogenic radionuclide isochron approach to determine a minimum age for the burial of a paleosol preserved within the CFF. Abundant palynomorphs in the paleosol are dominated by cool-climate taxa. Combining the paleosol burial age with a compilation of published and new CFF AAR data for marine bivalves Hiatella arctica and Mya truncata, we statistically define seven CFF aminozones and develop a piecewise isoleucine AAR calibration model for Baffin Island. From this, we estimate the minimum age of each aminozone, although the propagation of errors through all calculations produces large uncertainties for each age estimate. The youngest three CFF units, known as the Kogalu, Kuvinilk, and Cape Christian members, were most likely deposited during glaciations in the Mid- to Late-Pleistocene. The paleosol formed prior to 1.15 ± 0.20 Ma, and the underlying aminozones represent sedimentation during Early Pleistocene or latest Pliocene glaciations and record early advances of Laurentide ice across Baffin Island. © 2012 Elsevier B.V.